The directs impact to pre-filtering process to weather dataset - Al-Zyadat, Wa'el Jum'ah; Atan, Rodziah; Ibrahim, Hamidah; Azmi Murad, Masrah Azrifah (Asian Research Publication Network, 2011)
Monitoring through of data near real-time (dynamic data), in this paper, we address the issue of efficiently monitoring the satisfaction of sequential process to receive on the way to data storage. The research question then we is answer is how is it possible to monitor and efficiently fulfill the requirement of data storage by receiving a streaming of weather data? We propose a monitoring structural Algebra representing. We adapt the concept of data similarity in acclimated data from environment constraint a weather data from Malaysia. This enables contribute and construction of filtering data to doing the data meaningful and relevance. These performance enhancing techniques have general applicability.